Prevalence of Latent Tuberculosis Infection and its Associated Factors Among Diabetic Patients Availing Primary Health Care in Terengganu State, Malaysia - Nur Fatini Husain; Harmy Mohamed Yusoff; Nurulhuda Mat Hassan; Aniza Abdul Aziz (Oman Medical Journal, 2023)
Objectives: Diabetes mellitus (DM) patients are considered to be at high risk for contracting latent tuberculosis infection (LTBI). This study aimed to determine the prevalence of LTBI and its associated factors among diabetic patients attending primary care clinics in Terengganu state, Malaysia. Methods: This cross-sectional study was conducted among diabetic patients attending 11 health clinics in the Terengganu region from June 2017 to November 2018. The selected participants were administered a tuberculin skin test (TST). Simple and multivariate logistic regressions were applied to evaluate the significant associated factors of LTBI. Results: The total number of participants were 703 DM patients. The factors found associated with LTBI were poor diabetic control status (odds ratio (OR) = 8.53; p=0.008), being a healthcare worker (OR = 7.91; p=0.001), history of contact with TB patients (OR = 5.69; p < 0.001), bronchial asthma (OR = 5.28; p=0.019), coronary heart disease (OR = 3.45; p=0.026), and nephropathy (OR = 0.34; p=0.040). The presence of LTBI was found in 34 (4.8%) participants. Conclusions: At 4.8%, the prevalence of LTBI among DM patients in Terengganu is relatively low. Diabetics with poorly controlled blood glucose levels, nephropathy, bronchial asthma, coronary heart disease, history of TB patient contact, or working in the healthcare profession should be periodically tested for LTBI.